The Marketing Strategy Analysis in Local Films: A Case Study of the Macan dalam Toples Serial Film by Creative Economy Actors in Tasikmalaya Regency - Ramdani, Dwi; Nandang, Nandang; Rachmani, Nizza Nadya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the importance of the creative economy in enhancing regional competitiveness, particularly in the film subsector in Tasikmalaya Regency. The serial film Macan dalam Toples (MDT) by Layar Lokal is an example of the contribution of local creators, but it still faces challenges in audience retention and market expansion. The aim of the study is to analyze the marketing strategy of MDT through the 4P marketing mix (product, price, place, promotion) and a holistic marketing approach. The method used is qualitative, case study, including in-depth interviews, observations, and literature review. The results show that MDT builds emotional closeness with the local audience, but the inconsistent storyline lowers retention. The free pricing strategy is effective in reaching audiences, but it has not yet generated revenue. Distribution is through YouTube, but irregular release schedules weaken enthusiasm. Promotion via social media effectively reaches communities, but it is limited in expanding exposure. The holistic marketing analysis identifies four main constraints: 1) internal marketing is hindered by resource limitations, 2) relationships have not been optimized, 3) integrated marketing is weak, and 4) performance marketing is underutilized and difficult to measure for optimization. Based on these findings, it can be seen that the 4P strategy is strong but not yet optimal in increasing viewers and revenue. The application of holistic marketing offers a framework to improve content, distribution, and promotion.